DEVELOPING INFORMATION-ANALYTICAL COMPETENCE IN STUDENTS AS A FACTOR FOR PROTECTION AGAINST HARMFUL INFORMATION (Scientific journal of the Fergana State University, 2025)
This article explores the psychological and pedagogical factors involved in enhancing students’ personal information security within a blended learning environment. It highlights the importance of developing information-analytical competence in students as a key factor in safeguarding against the threat of harmful information. The article also examines the distinctive features, content, stages, and pedagogical conditions necessary for fostering this competence.